Mechanisms for resolving the agency problem in contemporary corporation - Selaković Radmila; Zvezdanović Milan (Ekonomski Pogledi, 2015)
Prevention of reduction in value of business assets or avoidance of yield losses for shareholders could be achieved by applying various mechanisms for solving agency problems. In order to reduce the management's deviation from shareholders' interests, shareholders could: 1) design compensation package for the management team, and 2) monitor the activities of management. Overcoming the agency's problems can be achieved: the division of responsibilities and control mechanisms between the management and the board of directors, increasing the level of transparency in defining the obligations and ways to reward management, increasing the ownership stake of shareholders with greater share in the equity and the replacement of inefficient management. The authors first present the agency problem and then analyze the ways of its resolving aimed at reducing or completely removing the conflict between shareholders and managers.